Studi Populasi dan Interaksi Sosial Monyet Ekor Panjang (Macaca fascicularis) di Kawasan Pura Pulaki, Bali - Jafron, Moh Jafron Syah (Universitas Sulawesi Barat, 2023)
Macaca fascicularis is a primate that has a wide distribution in Indonesia, one of which is the island of Bali. The habitat of M. fascicularis in Bali can be found in sacred areas such as Pulaki temple which is located in Gerokgak district, Buleleng regency. This study aimed to determine the population structure and social behaviors of long-tailed monkeys with humans in the Pulaki temple area.. The observation methods used in this study are Concentration count to calculate population structure, as well as ad libitum and scan animal sampling to observe daily behavior and social interactions. As a result of the calculation, the intermediate group consisted of 11 infants, 6 juveniles, 45 sub-adults, and 25 adults. The interaction of animals with humans observed in this study is agonistic and affiliation. Based on interviews with residents at the study site, it showed that respondents were accustomed to the presence of long-tailed monkeys so they considered not bothered by the presence of M. fascicularis. Some respondents also admitted that they often feed animals, but they agreed that a ban on feeding was imposed because it could interfere with traffic and endanger animals. The role of the community in conservation efforts of M. fascicularis in Pulaki temple is needed, one of which is by minimizing non-natural feeding to animals so that their natural behavior can be maintained. The natural behavior of animals that have changed can affect the balance of ecosystems due to changes in ecological niches.